2010
DOI: 10.1007/s11999-010-1481-7
|View full text |Cite
|
Sign up to set email alerts
|

Local Recurrence After Initial Multidisciplinary Management of Soft Tissue Sarcoma: Is there a Way Out?

Abstract: Patients with a local recurrence of a soft tissue sarcoma have a poor prognosis. Limb salvage and additional radiotherapy remain possible but with substantial complications. Amputation did not prevent additional local recurrence or death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 27 publications
(77 reference statements)
3
40
1
Order By: Relevance
“…At 5 years, primary soft tissue sarcomas of the extremities have a local recurrence rate of 6% to 17%, metastatic disease rate of 22% to 36%, and mortality rate of 24% to 33%. [30][31][32][33] Operative margin has been demonstrated to be the most important treatment factor and achieving negative margins is associated with decreased rates of local recurrence. 31,34 Histologic high-grade tumors are associated with increased local recurrence, metastasis, and mortality.…”
Section: Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…At 5 years, primary soft tissue sarcomas of the extremities have a local recurrence rate of 6% to 17%, metastatic disease rate of 22% to 36%, and mortality rate of 24% to 33%. [30][31][32][33] Operative margin has been demonstrated to be the most important treatment factor and achieving negative margins is associated with decreased rates of local recurrence. 31,34 Histologic high-grade tumors are associated with increased local recurrence, metastasis, and mortality.…”
Section: Prognosismentioning
confidence: 99%
“…5 Multiple studies have shown no difference in survival rates between limb salvage techniques verses amputation. 33,39 Epineural dissection has been demonstrated to be a safe technique that facilitates limb salvage, in particular in cases in which the soft tissue sarcoma abuts the sciatic nerve. 40 Some centers advocate for plastic surgery involvement for closure, particularly in the setting of irradiated tissue, with one study noting a trend toward decreased reoperation rates.…”
Section: Surgical Managementmentioning
confidence: 99%
“…Local recurrence rates after radiation and resection of soft tissue sarcoma have been reported as high as 20% [61, 62]; however, most modern series report the number at 10% or less [34, 35, 63, 64]. Local recurrence can be an extremely difficult problem to manage effectively.…”
Section: Treatmentmentioning
confidence: 99%
“…Patients who develop a local recurrence from a soft-tissue sarcoma have a poor prognosis [1,7,8]. One study suggests the development of a local recurrence is the most important factor associated with decreased survival, and once patients develop a local recurrence, they are about three times more likely to die from disease compared to patients who do not develop a local recurrence [6].…”
Section: Introductionmentioning
confidence: 99%
“…Novais et al [8] confirmed local recurrence independently predicts survival after adjusting for all major risk factors. Contemporary multimodal treatment of primary soft-tissue sarcoma reportedly reduces the incidence of local recurrence [1,6]. However, when it occurs, local recurrence remains a devastating event for patients and usually entails substantial morbidity.…”
Section: Introductionmentioning
confidence: 99%